1922
DOI: 10.1093/oxfordjournals.aob.a089817
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Abscission in Sea Island Cotton

Abstract: With fourteen Figures In the Text. INTRODUCTION.T HE immediate object of the studies reported in the present paper was to obtain information concerning both the external and the internal factors responsible for the premature shedding of the flower-buds and the young fruit (bolls) of the cotton-plant in St. Vincent. The economic importance of premature abscission is not, of course, confined to the cotton-plant, for it is responsible for considerable losses in a large number of cultivated plants. Future investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
22
0

Year Published

1932
1932
1987
1987

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 0 publications
3
22
0
Order By: Relevance
“…These results with the tomato are in complete agreement with those secured with cotton by MASON (17,18), who observed a marked retardation in growth of both the central stem and lateral branches during flowering and fruiting. The rate of elongation of the main axis of the plants decreased in exact proportion to the amount of flowers formed and fruits set.…”
supporting
confidence: 92%
“…These results with the tomato are in complete agreement with those secured with cotton by MASON (17,18), who observed a marked retardation in growth of both the central stem and lateral branches during flowering and fruiting. The rate of elongation of the main axis of the plants decreased in exact proportion to the amount of flowers formed and fruits set.…”
supporting
confidence: 92%
“…The results support the hypothesis that stresses decrease boll retention because they affect the hormonal balance in bolls and their abscission zones. Abscission of cotton (Gossypium hirsutum L.) fruits (bolls) is stongly affected by the balance between production of and demand for photosynthate (10,15,20). The early work of Mason (20) led to the nutritional theory of boll abscission which stated that "the cotton plant retains only as many bolls as it can supply with carbohydrates, nitrogen, or other nutrients" (6).…”
Section: Introductionmentioning
confidence: 99%
“…Abscission of cotton (Gossypium hirsutum L.) fruits (bolls) is stongly affected by the balance between production of and demand for photosynthate (10,15,20). The early work of Mason (20) led to the nutritional theory of boll abscission which stated that "the cotton plant retains only as many bolls as it can supply with carbohydrates, nitrogen, or other nutrients" (6). Research by Eaton and co-workers (7-9) indicated some inadequacies of the nutritional theory, and much of the subsequent research concentrated on hormonal regulation of abscission.…”
mentioning
confidence: 99%
“…This view of the cause of boll shedding is possibly quite old, but the first reference with which the writers are familiar is that of MASON (20) in 1922 in which he said that both the cessation of growth of the main axis and the augimiented susceptibility to shedding could be attributed to a correlation factor which tended to deflect the supply of elaborated food from the apical part of the plant to the fruit developing on the basal fruiting branches. In 1934 MWASON and PHILLIS (21) wrote that the bolls drain the vegetative plant of its food materials, the leaves yellow and fall off as nitrogen is drained away, and as the strain increases the flower-buds and bolls themselves are starved and shed.…”
mentioning
confidence: 99%
“…None of the foregoing conclusions was supported by original analytical data but it was known from earlier work that the nitrogen content of vegetative parts of the cotton plant declines with the advance of the summer. 1\ASONN (20) had found that the removal of all leaves caused a prompt shedding of nearly all young bolls carried by Sea Island cotton plants, and EATON (2) had found that when previously set bolls were removed from Upland plants these were replaced within a matter of 10 days with new bolls. HAWKINS et al (15) lfleasured the trends in carbohydrate levels in cotton plants throughout a summer and concluded in 1933 that the percentage of shedding is regulated by the amount of plant food available for the development of the young bolls.…”
mentioning
confidence: 99%